Augmented Reality: Ukrainian Present Business and Future Education - Мінтій, Ірина; Соловйов, Володимир (Pedagogy of Higher and Secondary Education, 2018)
Mintii I.S. and Soloviev V.N. Augmented Reality: Ukrainian Present Business and Future Education. The aim of the study: analysis of the current state and prospects for the development of augmented reality in Ukraine in business and education. The objectives of the study: to analyze the experience of using the augmented reality in advertising, marketing, education of Ukraine; to investigate the problems existing in this direction. The object of the study: the process of using augmented reality in advertising, marketing, education. The subject of the study: specific projects using the augmented reality in advertising, marketing, education. The used method of study was theoretical that included analysis of articles and materials of conferences on the research problem. The results of the study: nowadays, the augmented reality is used primarily in the field of advertising and marketing of Ukraine. As an example is the advertisement of Kyivstar (virtual tour around Ukraine, augmented reality quest), some of the Ukrainian companies have certain results in in this direction, for example, Augmented Pixels, Simo AR (in the development of a browser with augmented reality, the Kontramarka ticket service is implemented), Live Animations (such projects as Wonderland AR, My Yeti, Live Coloring, Gapchinska, Live Photo are already implemented). Among the problems that exist with the introduction of these technologies in education, first of all, we should note the shortage of specialists in the preparation of such educational projects and the uncoordinated actions of business and education in this direction. Main conclusions and recommendations: in order to disseminate research results it is necessary to hold thematic events of the all-Ukrainian level.